Interaction Design : beyond human-computer interaction - Rogers, Yvonne, ....-; Sharp, Helen, ....-; Preece, Jennifer, ....- (New Jersey : John Wiley and Sons, 2023)
Effective and engaging design is a critical component of any digital product, from virtual reality software to chatbots, smartphone apps, and more.In the newly updated sixth edition of Interaction Design: Beyond Human-Computer Interaction, a team of accomplished technology, design, and computing professors delivers an intuitive and instructive discussion of the principles underlying the design of effective interactive technologies. The authors discuss how to design and apply digital technologies in the real world, illustrated with numerous examples. The book explores the interdisciplinary foundations of interaction design, including skills from product design, computer science, human and social psychology, and others.The book builds on the highly successful fifth edition and draws on extensive new research and interviews with accomplished professionals and researchers in the field that reflect a rapidly-changing landscape. It is supported by a website hosting digital resources that add to and complement the material contained within
Keywords: digital design; human-computer interaction